The Pitfalls in Nonaqueous Electrochemistry of Al‐Ion and Al Dual‐Ion Batteries. Issue 45 (23rd October 2020) - Kravchyk, Kostiantyn V.; Kovalenko, Maksym V.
Abstract: The quest for cost‐effective and TWh‐scale stationary energy storage systems has caused a surge of research on novel post‐Li‐ion batteries that consist solely of abundant chemical elements. Nonaqueous Al batteries, inter alia, are appealing as an inexpensive electrochemical technology owing to the high natural abundance of aluminum. A critical assessment of the literature on Al batteries, however, points to numerous misconceptions in this field. The latter is primarily linked to the false assessment of the charge storage redox reactions occurring upon cycling of Al batteries. To ensure the constructive progress of Al batteries, in this essay, the current scientific understanding of the operational mechanisms of two commonly studied Al battery systems, Al‐ion and Al dual‐ion batteries are summarized. Furthermore, the main pitfalls in interpretation and reporting of the electrochemical performance of Al cathode materials and cell‐level energy densities of Al batteries are clarified along with core challenges currently limiting their development. Toward this end, the subject of the charge storage balancing of Al dual‐ion batteries is discussed. Abstract : This essay summarizes the current scientific understanding of operational mechanisms of the two most commonly studied Al battery systems, as Al‐ion and Al dual‐ion batteries. Furthermore, it outlines the main pitfalls in interpretation and reporting of the electrochemical performance of Al cathode materials and cell‐level energy densities of Al batteries along with the core challenges currently limiting their development.